Identification of Rice Genotypes Resistant To Bacterial Leaf Blight Disease Using Ssr Markers - Acharya, A.; Adhikari, N. R.; Amgain, R. B.; Poudel, A.; Yadav, R.; Poudyal, K. (Journal of the Institute of Agriculture and Animal Science, 2018)
Bacterial blight disease of rice is a growing and challenging concern in Nepal. Since bacterial pathogen (Xanthomonas oryzae pv. oryzae) is difficult to manage by other means effectively, development of host plant resistance is the most effective mean to control this disease. This study was carried out to identify the bacterial leaf blight resistant genotypes of rice by using of molecular markers linked with bacterial blight resistant genes. Sixty genotypes of rice were screened at glass house for BB resistance and they were tested for the presence of Xa4, Xa5, Xa7 and Xa21 genes using markers MP, RM122, M5 and pTA248 respectively. IRBB 60 and Jumli Marshi were used as resistant and susceptible check respectively. Twenty five genotypes of rice were detected with presence of Xa4 gene, 24 genotypes with Xa5 gene and fourteen genotypes with Xa7 gene. Twenty four genotypes did not showed presence of any gene. Twenty four genotypes showed the presence of more than one gene with the specific molecular markers. Almost all genotypes that did not show presence of any gene were found highly susceptible in greenhouse conditions with both inoculums. Genotypes having more than one BB resistance gene were found resistant in greenhouse conditions with both inoculums suggesting combination of BB resistance gene through gene pyramiding will provide BB resistant varieties in rice breeding.